2008
DOI: 10.1248/bpb.31.1483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amino Acids on Malarial Heme Crystallization

Abstract: To gain insight into the mechanism of malarial hemozoin formation and to explore various biological groups for screening novel antimalarial drugs, we examined the effects of amino acids on the formation of b b-hematin (BH), which is a synthetic heme crystal structurally identical to hemozoin, in vitro. Our results showed that BH formation was significantly inhibited by basic amino acids (arginine, lysine, and histidine), probably due to the abilities of these amino acids to complex with heme. The results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…The differences in morphology between dioleoyl-PC and dipalmitoyl-PC vesicles were probably due to their different physical properties, in particular the different states – fluid or gel – caused by the differences in T m values. Moreover, since the hydrophobic interactions between their inducers and heme have been proposed as an important force in the creation of a precursor heme dimer [38], [45], [54], [55], it was interesting to explore the correlation between the physical properties of phospholipids and their ability to induce BH. Our results demonstrated that phospholipids could induce BH formation only in the fluid phase, and could not do so in the gel phase.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in morphology between dioleoyl-PC and dipalmitoyl-PC vesicles were probably due to their different physical properties, in particular the different states – fluid or gel – caused by the differences in T m values. Moreover, since the hydrophobic interactions between their inducers and heme have been proposed as an important force in the creation of a precursor heme dimer [38], [45], [54], [55], it was interesting to explore the correlation between the physical properties of phospholipids and their ability to induce BH. Our results demonstrated that phospholipids could induce BH formation only in the fluid phase, and could not do so in the gel phase.…”
Section: Discussionmentioning
confidence: 99%
“…In another report, effects of amino acids on the formation of β -hematin (BH) was investigated, and results showed that BH formation was significantly inhibited by basic amino acids due to their abilities to complex with heme 31. Therefore, synthesized bisquinolines were assayed for inhibition of BH formation according to a procedure reported earlier 32.…”
Section: Resultsmentioning
confidence: 99%
“…Coincidentally, there is an association between severe malaria and Plasmodium falciparum haemozoin (HZ), a by-product of digested haemoglobin from P. falciparum infected erythrocytes, released into the bloodstream upon cell rupture [ 19 22 ]. Increase of l -Arg breakdown (free or intra-erythrocyte) has been reported elsewhere [ 23 ], while another report shows that l -Arg inhibits the formation of the synthetic pigment crystal (beta-hematin, βH) [ 24 ]. There is no information so far about a possible interaction between l -Arg and HZ.…”
Section: Introductionmentioning
confidence: 83%
“…Thus, an interaction between HZ and l -Arg can be expected. Indeed, Uyen and colleagues showed that basic amino acids, such as l -Arg or l -Lysine ( l -Lys), inhibit the formation of βH [ 24 ], the synthetic crystal made only of the haem portion of HZ, indirectly demonstrating the interaction of l -Arg with haem. However, in the present experiments, synthetic βH, differently from native HZ, was not able to reduce NO production even at the dose of 60 µM (Additional files 3 , 4 ) suggesting that the l -Arg–HZ interaction requires also a component of HZ, not yet identified.…”
Section: Discussionmentioning
confidence: 99%